2010
DOI: 10.1007/s10750-010-0256-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and success of ambush and chase predation in fish assemblages associated with seagrass and bare sediment in an Adriatic lagoon

Abstract: Predation of fish assemblages in seagrass meadows was examined in the field and in tank experiments. Lure trolling indicated that (1) total abundance of fish was higher on bare sediment where small fish (\5 cm), including juveniles, predominated; (2) abundance was lowest in seagrass where large fish ([15 cm) predominated; (3) large ambush predators, primarily the grass goby and European eel, were almost completely restricted to seagrass; (4) the predation mode in seagrass was almost entirely ambushing or stalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…This is contrary to the general situation where an increase in habitat complexity, understood as a greater availability of microhabitats, favours a greater abundance and diversity of associated fauna (Heck & Wilson, 1987;York et al, 2006;Gullström et al, 2008). However, quantitative habitat complexity not always increase the relative habitat value of SAV (Seitz et al, 2006;Bogut et al, 2007;Florido & Sánchez et al, 2010;Schultz & Kruschel, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This is contrary to the general situation where an increase in habitat complexity, understood as a greater availability of microhabitats, favours a greater abundance and diversity of associated fauna (Heck & Wilson, 1987;York et al, 2006;Gullström et al, 2008). However, quantitative habitat complexity not always increase the relative habitat value of SAV (Seitz et al, 2006;Bogut et al, 2007;Florido & Sánchez et al, 2010;Schultz & Kruschel, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…The batracoid Opsanus beta was the only species associated exclusively with SAV in Pantanos de Centla and seagrasses in other ecosystems (Schofield, 2003;Vega-Cendejas, 2004). The preference of the carnivore O. beta for epibenthic prey distributed in SAV and its stalking strategy are common in fish that are associated with this habitat (Schultz & Kruschel, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intermediate tactic is used by the stalk-attack predator that actively searches for prey item. Once a prey is detected, stalk-attack predator approaches furtively until the prey is within the attack range, which is medium, and makes a speed burst to capture it (Matsuda et al 1993;Horinouchi et al 2009;Schultz and Kruschel 2010).…”
Section: Predation Mortalitymentioning
confidence: 99%
“…Stationary visual census of fish assemblages using baited cameras in the shallow benthos of Mediterranean rocky reefs resulted in higher counts of cruise-chase predators as compared to surface dwelling predators, while ambush predator density remained low (Stobart et al, 2007). Schultz and Kruschel (2010) showed for a Mediterranean Zostera bed that the visibility and detectability of the ambush predator Zosterisessor ophiocephalus was positively affected by mobile bait presentation. Cardona et al (2007), simultaneously conducting mobile experimental fishing and mobile visual census in Mediterranean Posidonia seagrass, found that a third of the visually detected taxa could be hooked, but that the majority of fish hooked (98%) were wait-chase and cruise-chase predators, these being two of the groups that are rare in visual census studies (Table 1).…”
Section: Introductionmentioning
confidence: 98%